2011
DOI: 10.1007/s00203-011-0751-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial mer operon-mediated detoxification of mercurial compounds: a short review

Abstract: Mercury pollution has emerged as a major problem in industrialized zones and presents a serious threat to environment and health of local communities. Effectiveness and wide distribution of mer operon by horizontal and vertical gene transfer in its various forms among large community of microbe reflect importance and compatibility of this mechanism in nature. This review specifically describes mer operon and its generic molecular mechanism with reference to the central role played by merA gene and its related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 66 publications
1
63
0
1
Order By: Relevance
“…As heat shock proteins have been reported to be induced by toxic metals (Cassier-Chauva and Chauvat, 2015), five genes coding for heat shock proteins and five genes coding for chaperons identified in this study were suggested to be able to protect bacterial cells from Hg stress due that they are known to assist in protein folding and reintegration into the membrane. The mer operon is one of the most widely distributed in the Hg detoxification genetic system (Mathema et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…As heat shock proteins have been reported to be induced by toxic metals (Cassier-Chauva and Chauvat, 2015), five genes coding for heat shock proteins and five genes coding for chaperons identified in this study were suggested to be able to protect bacterial cells from Hg stress due that they are known to assist in protein folding and reintegration into the membrane. The mer operon is one of the most widely distributed in the Hg detoxification genetic system (Mathema et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The genetic system evolved as mer operon is the only well-known bacterial mercury resistance system with high yield transformation of its toxic target into volatile nontoxic forms [27,31,[33][34][35], particularly in Gram-negative bacteria [14,22]. The mer locus is found to be widely distributed among bacterial lineages, and mer-like sequences have been described.…”
Section: Pcr Amplification Of Mera Genementioning
confidence: 99%
“…The mer locus is found to be widely distributed among bacterial lineages, and mer-like sequences have been described. Several biochemical mechanisms are identified, and the complexity among the ecological niche of mercury-resistant microbes is still not fully described [10,35]. merA plays a key role on mercury resistance of bacterial community exposed to mercury contamination, but the combinatorial action of genetic determinants seems to confer a broad spectrum mercury detoxification system [10,35].…”
Section: Pcr Amplification Of Mera Genementioning
confidence: 99%
See 1 more Smart Citation
“…El mecanismo de resistencia más ampliamente descripto para este metal se basa en la presencia de grupos de genes organizados en un único operón, denominado "operón mer", que permite la detoxificación enzimática del metal conocido hasta el momento que permite la transformación de formas tóxicas a formas no toxicas volátiles (MATHEMA et al, 2011).…”
Section: Introductionunclassified